Ion-intercalation mechanism and structural relaxation in layered iron phosphate Na3Fe3(PO4)4 cathodes - Jakobsen, Christian Lund; Johansen, Morten; Ericsson, Tore; Häggström, Lennart; Christensen, Christian Kolle; Nielsen, Ida; Brant, William Robert; Ravnsbæk, Dorthe Bomholdt (Frontiers in Batteries and Electrochemistry, 2024)
Layered Na3Fe3(PO4)4 can function as a positive electrode for both Li- and Na-ion batteries and may hold advantages from both classical layered and phosphate-based electrode materials. Using a combination of ex-situ and operando synchrotron radiation powder X-ray diffraction, void space analysis, and Mössbauer spectroscopy, we herein investigate the structural evolution of the Na3Fe3(PO4)4 framework during Li- and Na-ion intercalation. We show that during discharge, Li- and Na-intercalation into Na3Fe3(PO4)4 occurs via a solid solution reaction wherein Na-ions appear to be preferentially intercalated into the intralayer sites. The intercalation causes an expansion of the unit cell volume, however at open circuit conditions after ion-intercalation (i.e., after battery discharge), Na3+xFe3(PO4)4 and LixNa3Fe3(PO4)4 undergo a structural relaxation, wherein the unit volume contracts below that of the pristine material. Rietveld refinement suggests that the ions intercalated into the intra-layer sites diffuse to the sites in the inter-layer space during the relaxation. This behavior brings new perspectives to understanding structural relaxation and deviations between structural evolution observed under dynamic and static conditions.